E-readiness and Entrepreneurship: A Cross Country Study of the Link between Technological Infrastructure and Entrepreneurial Activity - Richard L. Constand; Arthur H. Gilbert (The Journal of Entrepreneurial Finance (JEF), 2011)
This current study focuses on the relationship between a countrys e-readiness environment and entrepreneurial activities. Many government policies assume there is a direct causal relationship between e-readiness and entrepreneurial activity and some past studies have reported evidence supporting such a link. In this paper, a cross country panel data analysis using three different measures of entrepreneurial activity and different measures of e-readiness examines this relationship. The results of this study provide only weak support for the hypothesized relationship. Furthermore, the results appear to be very sensitive to the choice of proxy variables chosen to represent entrepreneurial activity and the different measures of e-readiness.
Keywords: H54; O32; M13; 650; e-readiness; entrepreneurship; technology infrastructure